Transmedia directors artistry, industry and new audiovisual aesthetics - Vernallis, Carol; Rogers, Holly; Perrott, Lisa (New York Bloomsbury Academic, 2020)
"Transmedia Directors focuses on artist-practitioners who work across media, platforms, and disciplines, including film, television, music video, commercials, and the internet. Working in the age of media convergence, today's em/impresarios project a distinctive style that points toward a new contemporary aesthetics. The media they engage with enrich their practices - through film and television (with its potential for world-building and sense of the past and future), music video (with its audiovisual aesthetics and rhythm), commercials (with their ability to project a message quickly), the internet (with its refreshed concepts of audience and participation), to larger forms like restaurants and amusement parks (with their materiality alongside today's digital aesthetics). These directors encourage us to reassess concepts of authorship, assemblage, transmedia, audiovisual aesthetics, and world-building"-- Provided by publisher
Includes bibliographical references (pages 450-483) and index.
Keywords: Motion pictures -- Production and direction; Music videos -- Production and direction; Television -- Production and direction